Development of Multimedia Based E-Folklore to Improve Reading Comprehension of Grade IV Elementary School - Jati, Adhy Rinasya; Purwati, Panca Dewi (Jurnal Prima Edukasia, 2024)
Reading comprehension involves one of the activities related to reading gain understanding of concepts, understand words, and understand ideas. One of the challenges in learning is that many students have not been able to master reading comprehension well. The purpose of this research is to establish the validation outcomes and efficacy of E-Folklore educational media. This research uses the ADDIE model. The subjects in this study include, 1 material expert, 1 media expert, 1 practitioner 6 22 large-scale pupils and 22 small-scale students. Researchers employ observation, interviews, tests, and questionnaires to gather data. Test questions and questionnaires were employed as data collection tools. The data analysis techniques used by researchers are qualitative and quantitative. The percentage of feasibility from material experts is 92.5%, media experts are 90%, and practitioner responses are 95.58% and student responses are 90.50% with an overall qualification of "Feasible". For small scale effectiveness of 0.373 while the large scale is 0.774, it can be concluded that there is an increase of 2.0% so that it can be categorized as effective. this research produces multimedia-based E-Folklore learning media efforts to improve student reading comprehension can be categorized as feasible.